Analysis of a High Power Density Axial Flux Permanent Magnet Synchronous Machine with Active Cooling - Jędryczka, Cezary; Mysiński, Michał; Pietrowski, Wojciech; Ziegler, Bartosz; Krakowski, Tomasz (XXVIII. Symposium Electromagnetic Phenomena in Nonlinear Circuits (EPNC 2024): Conference Proceedings, 2025)
The article discusses the synthesis and analysis of a high-power-density axial flux permanent magnet synchronous motor (AFPMSM) with active cooling. The research included electromagnetic and thermal analysis. In the electromagnetic part, numerical analysis employing 3D finite element method were carried out to analyze the influence of machine geometry and current density on the overall machine performance and the achieved power density. In the thermal approach, an active cooling concept with a cooling channel located in the winding was analyzed. Numerical thermodynamic models of the winding were developed, based on which the various approaches of the investigated solution were considered and their impact on improving the power density of the machine assessed.